2012
DOI: 10.5194/bg-9-875-2012
|View full text |Cite
|
Sign up to set email alerts
|

The imprint of surface fluxes and transport on variations in total column carbon dioxide

Abstract: Abstract. New observations of the vertically integrated CO 2 mixing ratio, CO 2 , from ground-based remote sensing show that variations in CO 2 are primarily determined by large-scale flux patterns. They therefore provide fundamentally different information than observations made within the boundary layer, which reflect the combined influence of large-scale and local fluxes. Observations of both CO 2 and CO 2 concentrations in the free troposphere show that large-scale spatial gradients induce synoptic-scale t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 53 publications
9
131
0
Order By: Relevance
“…The results for several latitude bands are summarised in Table 1, showing that the largest relative discrepancy is obtained for the southern temperate zone and that the best agreement is achieved for northern mid-and high latitudes where the satellite seasonal cycle is about 5 % larger compared with CarbonTracker. These seasonal cycle differences are similar to differences found between CarbonTracker and TCCON (Keppel-Aleks et al, 2012;Wunch et al, 2013).…”
Section: Seasonal Cycle Amplitudesupporting
confidence: 73%
“…The results for several latitude bands are summarised in Table 1, showing that the largest relative discrepancy is obtained for the southern temperate zone and that the best agreement is achieved for northern mid-and high latitudes where the satellite seasonal cycle is about 5 % larger compared with CarbonTracker. These seasonal cycle differences are similar to differences found between CarbonTracker and TCCON (Keppel-Aleks et al, 2012;Wunch et al, 2013).…”
Section: Seasonal Cycle Amplitudesupporting
confidence: 73%
“…The free troposphere spatial gradient also demonstrates a wave-like pattern. A previous study on the total column CO 2 from the groundbased TCCON found strong correlation between the midlatitude column CO 2 and synoptic-scale variation of potential temperature (θ , at 700 hPa), a dynamic tracer for adiabatic air transport (Keppel-Aleks et al, 2012). Thus, they also propose that the variations in column CO 2 are mainly driven by large-scale flux and transport.…”
Section: Influence Of Large-scale Circulationmentioning
confidence: 91%
“…This colocation methodology is based on the one used in Inoue et al (2013), with the exception that we replace the lat-long circle with a great-distance circle to avoid warping near the poles. Wunch et al (2011b) refined the geographical method by adding midtropospheric temperature at 700 hPa as an extra threshold to take advantage of the correlation between X CO 2 and midtropospheric temperature (Keppel-Aleks et al, 2011, 2012. Their colocation methodology locates and averages all ACOS-GOSAT observations falling within ±30 • longitude, ±10 • latitude, ±5 days, and ±2 kelvin in T 700 .…”
Section: Comparison To Existing Methodologiesmentioning
confidence: 99%